Beliefs and Leadership in World Politics
XIV, 288 p. 1 illus.
Keywords: Focusing on how policy makers make decisions in foreign policy, this book examines how beliefs are causal mechanisms which steer decisions, shape leaders and perceptions of reality, and lead to cognitive and motivated biases that distort, block and recast incoming information from the environment.